Analisis Kinerja Keuangan Usaha Sawmill Vina Lestari Jaya Di Tenggarong - Syahruddin Syahruddin (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2015)
Abstract:The purpose of this study was to determine the outline and assess the Company's financial performance Vina Lestari Jaya in 2004 compared to 2003 in terms of liquidity, solvency and profitability. How data collection techniques include interviews, observation and collection of data related to the data business, particularly financial data. Based on the analysis that has been submitted, it can be concluded that the hypothesis which says,